Effect Of Additional Probiotic Bulter Of Multi Cell In Water Media With Different Dosage To Decrease Of Amoniak Concentration, Growth And Life Growth Improvements Green Catfish(Mystus Nemurus) - Yusman Zega; Niken Ayu Pamukas; Usman M. Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was condureted from February 5th,2018 –March 7th,2018 inAquaculture Technology Laboratory, Fisheries and MarineFaculty, University of Riau. This study aims to determine the optimum doses of probiotics boster multi cells to decrease the concentration of ammonia, growth and survival of green catfish (Mystus nemorus). The method used in this research was Complete Randomized Design (CRD) with the one factor, five treatments levels and 3 replications. The results showed the best probiotic treatment was P2 (5 ml / m3), with ammonia decrease of 0.0020-0,0025 mg / L, absolute weight growth of 17,17 g, daily growth rate of 3,67, and survival rate of 85%. Keywords :Ammoniac,Boster multi cells, Green Catfish (Mystus nemurus), Growth, Probiotic.